PTU-014 Does adherence to the BSG endorsed decompensated cirrhosis care bundle improve patient outcomes?. (June 2019) - Johnston, Alexander J; Chen, Hayley; Palmer, Andrew; O'Sullivan, Tim; Clark, Paul
Abstract : Introduction: A BSG-endorsed care bundle for the management of decompensated cirrhosis in the first 24 hours of admission has been implemented in the North East of England resulting in improved management of these patients; however in this study patient outcomes were not followed up and there have been no subsequent published studies of its use. 1, 2 In our expanding hepatology unit of a small tertiary hospital in Brisbane, Australia we reviewed inpatient management of decompensated cirrhotic patients to assess morbidity, mortality and if adherence to the care bundle improves patient outcomes. Methods: We retrospectively reviewed patient notes for hospital admissions due to decompensated cirrhosis between 1/6/16 – 1/6/17. Admissions were scored according to care bundle adherence and divided into tertiles. Mortality, rates of readmission and inpatient length of stay (LOS) were compared between the most adherent and least adherent groups using Fisher's exact test with p values < 0.05 considered significant. Results: 59 admissions were reviewed consisting of 39 patients (69% male, median age 60 years) with a median MELD 19. Only Child-Pugh B (33/59, 56%) and C (26/59, 44%) patients were included. The most adherent group had numerically lower 1-year mortality (5/16, 31%) than the least adherent group (7/15, 47%, p=0.4725). Readmission rates within 1 year were reduced in the most adherent group (6/17, 35%) compared to the least adherent group (8/16, 50%), though not statistically significant (p=0.4905). Readmission rates at 30 days and 6 months were also reduced with care bundle adherence however again were not statistically significant. There was no effect on the length of hospital stay between groups. Conclusions: Our results suggest reduced mortality and hospital readmission in patients more closely adherent to the BSG care bundle, however this difference did not reach statistical significance. Reasons for this include a small sample size which limited statistical power and that overall adherence to the care bundle was poor. Following this study, we plan to implement a care bundle systematically to further evaluate patient outcomes. References: McPherson, S., Dyson, J., Austin, A. & Hudson, M. Response to the NCEPOD report: development of a care bundle for patients admitted with decompensated cirrhosis—the first 24|h. Frontline Gastroenterol . 7, 16–23 ( 2016). Dyson, J. K. et al. Implementation of a 'care bundle' improves the management of patients admitted to hospital with decompensated cirrhosis. Aliment. Pharmacol. Ther . 44, 1030–1038 ( 2016).